Living alone and loving it : a guide to relishing the solo life - Feldon, Barbara (Fireside, 2003)
After a relationship impasse, Barbara Feldon -- universally known as the effervescent spy "99" on Get Smart -- found herself living alone. Little did she know that this time would become one of the most enriching and joyous periods of her life. Now Feldon shares her secrets for living alone and loving it. Prescribing antidotes for loneliness, salves for fears, and answers for just about every question that arises in an unpartnered day, she covers both the practical and emotional aspects of the solo life, including how to: Stop imagining that marriage is a solution for loneliness • Nurture a glowing self-image that is not dependent on an admirer • Value connections that might be overlooked • Develop your creative side • End negative thinking Whether you are blessed with the promise of youth or the wisdom of age, Living Alone & Loving It will instill the know-how to forge a life with few maps and many adventures.